Compound Metacurl Antenna With C- and N-Type Metaatoms - Hisamatsu Nakano; Tomoki Abe; Amit Mehta; Junji Yamauchi (IEEE Access, 2020)
A metacurl antenna made of C-type metaatoms (forming a C-type metaline), called the C-metacurl antenna, is investigated. The investigation reveals that the gain for a left-handed circularly polarized wave, LHCP gain, has a maximum value at frequency fLH and the gain for a right-handed circularly polarized wave, RHCP gain, has a maximum value at different frequency fRH, where the maximum LHCP gain is smaller than the maximum RHCP gain. Subsequently, a different metaatom that forms the unit cell of an N-type metaline, called the N-type metaatom, is investigated. It is found that the radiation from the N-type metaatom is LHCP. This infers that the maximum LHCP gain for the C-metacurl antenna will increase when some C-type metaatoms are replaced by N-type metaatoms. Based on this inference, a novel metacurl antenna composed of C-type metaatoms and N-type metaatoms, called the compound metacurl antenna, is analyzed. The analysis reveals that replacement with an appropriate number of N-type metaatoms increases the maximum LHCP gain, resulting in a balancing of LHCP gain and RHCP gain. The antenna characteristics under such a gain-balanced situation, including the radiation pattern, axial ratio, and input characteristic (VSWR), are also discussed.